Risk factors associated with substance abuse and disruptive behavior disorders: A cross-sectional study among undergraduates of the University of Ibadan, Nigeria (Nursing and Health Sciences Journal (NHSJ), 2025)
Substance abuse and disruptive behavior disorders (DBDs) are prevalent among university students and have significant health consequences. Despite various educational interventions on substance abuse, engagement in these behaviors remains high. This study assessed the factors associated with substance abuse and DBDs among undergraduate students at the University of Ibadan. A descriptive cross-sectional study design was employed, with 345 undergraduates selected. Data were collected using a structured questionnaire, cleaned, and analyzed using SPSS version 27.0. Descriptive statistics were presented in tables and figures, while Chi-square tests assessed associations between variables at p≤0.05. The study revealed that 64% of respondents had good knowledge of substance abuse and DBDs, and the prevalence of substance abuse and disruptive behaviour disorders among the students was 42%. Factors identified by students associated with substance abuse and disruptive behaviour disorders include Peer influence and academic stress, with most respondents claiming the assertions (150 (95%) and 129(82%) respectively). Additionally, sociodemographic factors such as religion (χ² = 20.659, p = 0.001), ethnicity (χ² = 11.324, p = 0.023), and financial support (χ² = 19.410, p = 0.001) were significantly associated with knowledge of substance abuse and DBDs. The study findings highlight the need for campaigns to create awareness about substance abuse and its effects among students and for the strict enforcement of substance abuse regulations. Universities should collaborate with all stakeholders, including student organisations, faculty staff, family, and local community organisations, to address underlying factors contributing to substance abuse and DBDs among students.